COMPARATIVE EFFICACY OF MORTAL AND VITAL METHODS OF CATTLE CHORIOPTOSIS LABORATORY DIAGNOSTICS - Kovalenko, S. (Scientific Progress & Innovations, 2021)
One of the most important conditions for the successful and efficient development of dairy and meat cattle breeding, as well as improving the quality of products is the fight against bovine parasitoses. Among animal ectoparasitoses, one of the most common acaroses is cattle chorioptosis caused by parasitizing Chorioptes bovis skin mites. Mites have a mechanical and toxic effect on the skin, creating conditions for the development of secondary micro-flora. They also cause irritation of nerve terminals and atrophy of the skin sebaceous glands. Epizootological well-being is possible under the conditions of monitoring studies using effective, highly sensitive methods for detecting chorioptosis pathogens. The aim of the research was to establish the effectiveness of existing vital and mortal methods of Chorioptes bovis Gerlach, 1857 laboratory diagnostics in the comparative aspect. Experimental studies were conducted in the Laboratory of the Department of Parasitology and Veterinary and Sanitary Expert Examination of Poltava State Agrarian University and also at the LLC “Komyshuvata Dairy Complex” of Krasnohrad district, Kharkiv region. Three vital methods (of A. V. Alfimova using vegetable oil; using bischofite and glycerin) and three mortal methods (scraping maceration, compressor, and flotation) of cattle chorioptosis laboratory diagnostics were tested. The main indicator of the diagnostic methods’ efficacy was the value of the invasion intensity. According to the results of acarological studies, it was found that the most sensitive vital method of cattle chorioptosis laboratory diagnostics was the method of scraping maceration. This method exceeded the effectiveness of the compressor method by 59.85 % and the flotation method by 67.0 1%. The most sensitive vital method for cattle chorioptosis laboratory diagnostics was the method of using bischofite and glycerin. This method exceeded the efficacy of the method with the use of vegetable oil by 7.97 % and the method of A. V. Alfimova – by 59.05 %. Its high diagnostic effectiveness in in case of chorioptosis has been established in comparison with the mortal method of scraping maceration (by 35.05 %). The obtained data enable to recommend the vital method with the use of bischofite and glycerin for the effective diagnostics of cattle chorioptosis.